The 7th International Conference on Information Technology 2015
DOI: 10.15849/icit.2015.0100
|View full text |Cite
|
Sign up to set email alerts
|

How Infographic should be evaluated?

Abstract: With a little time and too much information to learn, Infographics were used to support as data visualization. Visual communication is communication through visual aids. Visual communication is more effective than reading and hearing information. There are so many infographics for everything; however, how can we know which one has a good or not so good design. The aim of the paper is to clarify the evaluation approach of infographic in many aspects and methods. The paper presents the definition and the uses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 3 publications
1
28
0
4
Order By: Relevance
“…Also the content of the relevant course should be analysed at the highest level, that message design principles should be taken into consideration and that the infographic should consist of up-to-date information. Likewise, a study conducted by Siricharoen and Siricharoen (2015) emphasised that mental effort is needed in the design of infographics to determine how the purpose and data could be best transferred to the target group and that the elements in infographics should support the information process. The research found that all elements in the infographic (lines, colours, etc.)…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Also the content of the relevant course should be analysed at the highest level, that message design principles should be taken into consideration and that the infographic should consist of up-to-date information. Likewise, a study conducted by Siricharoen and Siricharoen (2015) emphasised that mental effort is needed in the design of infographics to determine how the purpose and data could be best transferred to the target group and that the elements in infographics should support the information process. The research found that all elements in the infographic (lines, colours, etc.)…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Here, we have used content analysis, infographic presentation (Lankow et al, 2012;Siricharoen & Siricharoen, 2015;Smiciklas, 2012), and exploratory research method to achieve the goal of this study (Stoeckli et al, 2018;Zavolokina et al, 2016). The relationships between the data are presented in different infographic tools, such as graphs, charts, and tables (Siricharoen & Siricharoen, 2015).…”
Section: Data Analysis and Interpretationmentioning
confidence: 99%
“…Pada penelitian dengan judul How Infographic should be evaluated? (Siricharoen & Siricharoen, 2015), infografis harus dapat menyampaikan informasi yang kompleks namun dapat mudah dan cepat memahamkan pembaca dengan cara menarik. Informasi yang disampaikan harus berupa fakta nyata, dengan data aktual dari sumber terpercaya.…”
Section: Pendahuluanunclassified